Kesadaran Hukum Masyarakat Kota Ruteng terhadap Pengelolaan Sampah Rumahtangga Ditinjau dari Peraturan Daerah Manggarai Nomor 2 Tahun 2013 tentang Pengelolaan Sampah - Maria Lidia Dumang; Jimmy Pello; Rudepel Petrus Leo (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
Low legal awareness of the community in household in Household waste management is a long-stunding issue in Ruteng City, in 2017-2018, it was once one of the dirties cities in Indonesia according to the Ministry of Environment and Forestry. The main problem in this research is the Legal Awarness of Ruteng City Community and the Implementationof Sanction againts Waste Managemnet Actors. The study is an empirical legal research that examines all legal events that occur in society through case and statute approaches. Data collection was conducted through three methods: interview, observations, and document study. The result show that low legal awarness of the community is influenced by law factors, law enforcement, infrastructure, community, and culturals.The impelemntation of criminal sanction is not yet firm and so far only warning sanction have been applied. Therefore, the recommendatons for this research are to increase legal awarness through government community implementing sanction firmly to enhance law enforcement.